Numerical algorithms for detecting embedded components. (September 2017) - Krone, Robert; Leykin, Anton
Abstract: We produce algorithms to detect whether a complex affine variety computed and presented numerically by the machinery of numerical algebraic geometry corresponds to an associated component of a polynomial ideal.